2021
DOI: 10.1007/s00705-021-05191-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel Tombusviridae species isolated from Paris polyphylla var. yunnanensis

Abstract: A novel virus, Paris virus 2 (ParV2), was isolated from diseased Paris polyphylla var. yunnanensis, and its complete genome sequence was determined and analyzed. ParV2 is a positive-sense single-stranded RNA (+ssRNA) virus with a genome size of 4118 nucleotides. The ParV2 genome contains six putative open reading frames (ORFs) that encode proteins with predicted molecular weights of 40.14, 100.26, 7.31, 7.85, 26.09, and 8.77 kDa. The rst ORF (ORF1) of ParV2 encodes a putative protein of 40.14 kDa (p40, nt: 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Total nucleic acids were isolated from leaves of the samples using a CTAB-based method ( Li et al, 2008 ) for determination of infection rate of each of ten viruses infecting Paris spp. These viruses included seven viruses (ParPV-3, ParPV-4, ParNV-1, HCRV, LycMoV, PMNV, and ParV1) identified by HTS in this study and three viruses (ChiVMV, PMMoV and PPVX) that were not found in this study but reported previously ( Wen et al, 2019 ; Chen et al, 2021 ; Yang et al, 2022 ). All the samples (20 HTS and 103 additional samples) collected from the four counties were tested individually for each of the target viruses.…”
Section: Methodssupporting
confidence: 60%
See 4 more Smart Citations
“…Total nucleic acids were isolated from leaves of the samples using a CTAB-based method ( Li et al, 2008 ) for determination of infection rate of each of ten viruses infecting Paris spp. These viruses included seven viruses (ParPV-3, ParPV-4, ParNV-1, HCRV, LycMoV, PMNV, and ParV1) identified by HTS in this study and three viruses (ChiVMV, PMMoV and PPVX) that were not found in this study but reported previously ( Wen et al, 2019 ; Chen et al, 2021 ; Yang et al, 2022 ). All the samples (20 HTS and 103 additional samples) collected from the four counties were tested individually for each of the target viruses.…”
Section: Methodssupporting
confidence: 60%
“…The spherical particles were measured to be 25–30 nm in diameter ( Figure 2A ), and filamentous particles were 700 ~ 800 nm in length ( Figure 2B ). The results indicated that viruses with spherical shape, besides viruses with filamentous shape ( Dong et al, 2007 ; Lan et al, 2018 ; Wen et al, 2019 ; Chen et al, 2020 , 2021 ; Yang et al, 2022 ), were associated with the viral diseases of P. yunnanensis .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations